Can Training Enhance Public Employees' Public Service Motivation? A Pretest–Posttest Design. (March 2021) - Chen, Chung-An; Hsieh, Chih-Wei; Chen, Don-Yun
Recent evidence shows public service motivation (PSM) may be unrelated to one's consideration of a public service career. In places where civil service examinations prevail, even adverse selection (selecting low-PSM individuals) can occur. This leaves public sector managers with tough questions: "Can we improve new recruits' PSM? Does training matter?" The present study attempts to answer these questions by using a case of onboard training in Taiwan. We hypothesize that PSM, along with public service–related knowledge and a positive attitude toward public service work, improves after training, and that the improvement hinges on trainees' satisfaction with training and perceived usefulness of training. Analytical results indicate that knowledge and attitudes are more "trainable" than PSM. Meanwhile, training satisfaction is associated with the growth of public service–related knowledge, while perceived training usefulness relates to a positive attitude toward public service work and PSM. Overall, these findings advance our understanding of the effectiveness of public service training, its determinants, and the implications for public employees' public service orientations.